2013
DOI: 10.1016/j.tox.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene-induced formic aciduria: Effect of dose, sex and strain of rat

Abstract: Yaqoob, N, Evans, AR and Lock, EATrichloroethylene-induced formic aciduria: effect of dose, sex and strain of rat.http://researchonline.ljmu.ac.uk/1383/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…To date, there is no consensus on TCOH-induced kidney toxicity, but it may be resulting through perturbation of formate metabolism. The oxidative metabolites of TCE, TCA and TCOH, are known to mediate formic aciduria in rats (Yaqoob et al 2013) and mice (Lock et al 2017). It was also reported that TCE, but not TCOH, can induce elevated renal injury markers in rats after 12 weeks of exposure (Yaqoob et al 2014), even though both chemicals can cause formic aciduria in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no consensus on TCOH-induced kidney toxicity, but it may be resulting through perturbation of formate metabolism. The oxidative metabolites of TCE, TCA and TCOH, are known to mediate formic aciduria in rats (Yaqoob et al 2013) and mice (Lock et al 2017). It was also reported that TCE, but not TCOH, can induce elevated renal injury markers in rats after 12 weeks of exposure (Yaqoob et al 2014), even though both chemicals can cause formic aciduria in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades, worldwide studies about the occupational epidemiology, prevention, and pathogenesis of THS have been published, but the mechanism remains unclear (Gilbert et al, 2016; Jiang et al, 2014; Yaqoob et al, 2013). Many scholars argued that skin lesions and organ injury caused by TCE belong to type IV hypersensitivity (Huang et al, 2015; Xu et al, 2011), and the injury is mainly mediated by T and B lymphocytes (Dai et al, 2006).…”
Section: Cellular Immunity Of Tcementioning
confidence: 99%